Agricultural Land Management Based On Local Arisival Of The Kaili Da’a Tribe In Dombu Village - Juraid; Wahyuni; Ika Listiqowati (International Journal of Science, Technology & Management, 2021)
This study aims to describe the local wisdom of the Kaili da’a Tribe in managing agricultural land in Dombu Village, Marawola District, Sigi Regency, Central Sulawesi. This research is descriptive qualitative, the research subjects in this study are the people of the Kaili da’a Tribe in Dombu village with the key informant of the Kaili da’a tribal chief, the types and sources of data are primary data and secondary data with data collection methods through observation and interviews. Qualitative descriptive data analysis technique. The results of this study indicate that the cultivation of agricultural land is carried out traditionally in accordance with the local wisdom of the Kaili da’a Tribe, while the management of agricultural land of the Kaili da’a Tribe includes: 1) Preparation includes customary council meetings and traditional ceremonies, 2) Land Opening, 3) Plowing of Land, 4) Land Harvesting, 5) Basic Fertilization.